The integration of primary education and training issues unique features - Umirkhujayeva Sumayyo Ibrogim qizi (Zien Journals, 2021)
The use of interactive methods of teaching in the educational process, the position of manager of the educational process, in which the purpose of management education as a subject and an object of pupils will be transferred. Hence, the content of pedagogical technology education occurs on the basis of methods, forms and means. In the process, guaranteed results in the EIA directed.
Keywords: pedagogical technology; innovation; integration; pedagogical monitoring